MODEL PEMBELAJARAN INKUIRI TERBIMBING PADA MATA KULIAH MIKROBIOLOGI DASAR DI PERGURUAN TINGGI BERBASIS VOKASI - Ulimaz, Almira (Nusantara Hasana Journal, 2022)
Vocational colleges have diverse human resources. Students who enter vocational colleges mostly come from high schools whose majors are different from the majors they took on the campus. This will have an impact especially if they have never studied the basics of the course. One of the subjects that is difficult to learn is Primary Microbiology. Based on the results of interviews with several students from three different years, it is known that they are quite difficult to understand the concept of the course. This study is descriptive qualitative research. The data were taken from the results of observations, interviews, and also theoretical studies from the literature review. The method used in this research is grounded research. The results showed that learning on vocational campuses, especially in teaching and learning activities of Basic Microbiology requires a learning model in which students play a role and think actively in solving a problem. The guided inquiry model is the most suitable learning model to be applied in the learning process in vocational colleges with student backgrounds whose basic secondary school education is diverse. This is because this model emphasizes collaboration in solving problems in groups and building knowledge independently.